AL-QUR’AN DAN KECERDASAN SPIRITUAL: UPAYA MENYINGKAP RAHASIA ALLAH DALAM AL-QUR’AN - Idaman Idaman; Samsul Hidayat (Khatulistiwa, 2011)
This article attempts to describe the phenomena of spiritual quotient by referring to several stories which still contain unrevealed secrets in the Qur‟an. Spiritual quotient is a form of intelligence that uses spiritual process or in the Islamic mystical term called irfani. Moslem great mystics in the past used irfani method to elaborate Allah‟s secrets in the Qur‟an. The method of understanding Quranic verses using the irfani medium is called irfani interpretation method. By using this method, Sufis interpret Allah‟s verses based on their thought, behavior and spiritual light. Undeniably, those Sufis were also influenced by their own culture or cultural characters such as those of the Persian, Indian and Greek. Islamic mystics who usually used this method in their interpretation of the Qur‟an were Ibn „Arabi, Mansur al-Hallaj, Jalaluddin Rumi, Imam al-Ghazali, Syihabuddin Suhrawardi al-Maqtul, etc. Thus, revealing the Quranic secrets not only followed the procedure of interpretation that had existed before, namely naqli and aqli interpretation, but also used spiritual ability and spiritual quotient. They (Islamic mystics) not only see and understand the literal meanings but also the spiritual meanings of Allah‟s message.